Testing for SARS-CoV-2 Infection in Care Home Residents and Staff in English Care Homes: A Service Evaluation - Julii Brainard; Clare Aldus; Emma Smith; Sharon Dunham; Paul Hunter; Nicholas Steel; Paul Everden (Journal of Long-Term Care, 2022)
Context: COVID-19 is especially dangerous to older adults living in residential care.